Low hemoglobin levels are associated with direct antiglobulin test positivity in patients with acute-on-chronic liver failure. (October 2021) - Shi, Linxi; Qin, Wanyuan; Mei, Cheng; Xu, Wei; Deng, Ying; Yin, Wenyu; Zhou, Rongrong; Fan, Xuegong; Li, Ruixuan; Peng, Fang; Huang, Zebing; Li, Ning
Abstract: Background: Multiple factors contribute to anemia in patients with Hepatitis B virus (HBV)related acute-on-chronic liver failure (ACLF); however, the mechanism is unclear. The purpose of this study was to evaluate the clinical significance of the direct antiglobulin test (DAT) in patients with HBV related ACLF. Methods: DAT was used to detect immunoglobulins and/or complement proteins on the surface of erythrocytes. Results: We recruited 78 HBV-associated ACLF patients, 30 chronic hepatitis B(CHB)patients and 40 healthy people between October 2015 and May 2016. In HBV related ACLF patients, the hemoglobin concentration, number of erythrocytes, and hematocrit value were significantly lower, while the erythrocyte distribution width was significantly higher, compared to patients with CHB and healthy controls (HCs) (P < 0.001). The rates of DAT positivity in HBV related ACLF patients, CHB patients, and HCs were 62.8 %, 13.3 %, and 0%, respectively. DAT-positive ACLF patients exhibited lower Hb levels, older average age, as well as higher total bilirubin, alanine aminotransferase, and complement component 3 levels compared to DAT-negative patients. Conclusions: HBV related ACLF patients showed significant alterations in erythrocyte parameters, possibly reflecting disease development and severity. The high presence of erythrocyte autoantibodies suggested that immunologic clearance of erythrocytes contributed to multifactorial anemia in HBV related ACLF patients.